Neuropsychiatric Alterations in a Patient Diagnosed with Advanced Korsakoff’s Syndrome: Clinical Case of Low Incidence and Prevalence in Colombia (2022)
Korsakoff’s syndrome (KS) is an insidious and progressive neuropsychiatric disorder that affects specific neurocognitive functioning, especially in tasks that require sustained attention, memory, executive functions, and visuospatial functioning. Usually, this disease generates neuropsychiatric complications that worsen the quality of life (QOL) of patients in the medium term. We present a case of a 63-year-old male who presented with a diagnosis of advanced Korsakoff’s syndrome and has a clinical history of recurrent memory loss and a history of alcohol abuse. The patient showed difficulty manipulating immediate information, associated with a possible frontal lobe dysfunction, and inability to remember material given through the auditory pathway. The patient showed a psychiatric clinical picture which is constantly worsening his and his immediate caregiver’s QOL. The data obtained demonstrate that the patient presents a progressive cognitive impairment, which in the short term is correlated with Korsakoff-type dementia. It is suggested to carry out functional neurorehabilitation plans aimed at improving the QOL of the patient, his immediate caregiver, and future people with this type of diagnosis.